Developing Measurements for Creating Shared Value (CSV): Aspects and Indicators - Suripto Suripto (Jurnal Ilmiah Akuntansi, 2024)
This research aims to develop a Creating Shared Value (CSV) measurement that fulfills a sustainable context and avoids overlap. The study initially identifies two key aspects—business and social—comprising 27 indicators. Through further analysis, the research conceptualizes CSV measurement by incorporating an additional environmental aspect. This development addresses existing gaps by enhancing CSV disclosure aspects to more accurately assess the level of CSV disclosure. By fulfilling the sustainability context based on legitimacy theory, this approach can help companies gain legitimacy and support from stakeholders, thus enabling them to compete globally. The research employs a rigorous methodology to ensure that the new CSV measurement framework is robust and comprehensive. The findings suggest that a multidimensional approach to CSV, which includes business, social, and environmental aspects, provides a more holistic view of a company's efforts to create shared value. This refined CSV measurement can serve as a valuable tool for companies seeking to improve their sustainability practices and enhance their accountability to stakeholders.